Solve for x: (3a−b)/(x−b)=1/(x+1) ,if a≠( b+1)/3

Question

Solve for x:

(3a−b)/(x−b)=1/(x+1) ,if a≠( b+1)/3

in progress 0
Katherine 2 weeks 2022-01-12T15:36:25+00:00 1 Answer 0 views 0

Answers ( )

    0
    2022-01-12T15:38:20+00:00

    Answer:

    Step-by-step explanation:

    \frac{(3a-b)}{(x-b)}=\frac{1}{(x+1)}\\\\(3a-b)*(x+1)=1*(x-b)\\\\

    Use FOIL method

    3a*x + 3a*1 – b*x -b*1 = x – b

    3ax + 3a -bx – b = x -b

    3ax – bx -x + 3a – b = -b

    x*( 3a – b – 1) + 3a – b = -b

    x*( 3a – b – 1) = – b – 3a + b

    x*( 3a – b – 1) = -3a

    x=\frac{-3a}{( 3a - b - 1)}

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )